Improving the Engraftment Activities of Cryopreserved Human Umbilical Cord Blood Through the Development of Novel Glyco(peptide)-Based Aryl Ice Recrystallization Inhibitors - Adam, Madeleine Katrina (Université d'Ottawa / University of Ottawa, 2020)
The ability to preserve samples (e.g. biological substances) for extended periods has enabled many medical and industrial advancements including the development of blood banks and improvements to food storage. Cryopreservation, a biopreservation technique where samples are stored between -80 °C to -196 °C, allows for increased storage times of weeks to years for various cell types such as hematopoietic stem and progenitor cells (HSPCs). Cryopreserved HSPCs from human umbilical cord blood (UCB) can be used for hematopoietic stem cell transplantation used to treat over 80 diseases. Cryoprotectants like dimethyl sulfoxide are implemented to protect cells from cryoinjuries during cold storage; however, they fail to address phenomena that result in considerable loss of viable and functional cells after thawing. For instance, ice recrystallization occurring during cryopreservation involves the growth of larger ice crystals from smaller ones and this process is a substantial contributor to cellular damage. Along with the inability to mitigate ice recrystallization, numerous conventional cryoprotectants are toxic and lead to adverse outcomes to the cellular products undergoing preservation and to the recipients of the corresponding treatments. There is, therefore, tremendous interest in the development of novel non-toxic cryoprotectants able to reduce ice recrystallization during the storage of cellular products. That being said, the design and analysis of these ice recrystallization inhibitors (IRIs) are paramount for future innovations in regenerative and transfusion medicines. Over the past two decades, the Ben laboratory has designed a collection of IRIs originally inspired by the naturally occurring biological antifreezes (e.g. antifreeze glycoproteins, AFGPs) found in a variety of cold-tolerating animals (e.g. fish and insects). From the development of these IRI-active AFGP analogues came a series of carbohydrate-based small molecules found to improve the post-thaw properties of cells in vitro when used as cryosupplements during cryopreservation. The class of N-aryl-D-gluconamide IRIs, for example, has been shown to increase the post-thaw viability and function of HSPCs from UCB in small scale experiments. Notably, the impact of these cryoadditives on the post-thaw in vivo activities of cryopreserved cells had yet to be determined and this analysis would offer true insight into the clinical relevance of IRIs as cryoprotectants. Consequently, the research described herein marks the first time the in vivo significance of using IRIs during cryopreservation has been investigated. Specifically, this thesis reports both the in vitro impact (viability and functionality of cells post-thaw) as well as the in vivo impact (the engraftment activity of grafts in a xenotransplantation model) of using N-aryl-D-gluconamides for the cryopreservation of HSPCs from UCB. Moreover, through structure-activity relationship (SAR) studies of the N-aryl-D-gluconamides, a series of novel analogues were developed including derivatives with modified aryl and carbohydrate components. These analogues were analyzed for their IRI activity and cytotoxicity, and the promising candidates were assessed for their cryoprotectant abilities. Finally, an innovative approach to the development of IRI-active glyco(peptides) is achieved through the design of macromolecular AFGP analogues possessing unique physicochemical properties. This included the development of IRI-active materials able to self-assemble in solution as well as the production of carbohydrate-based surfactants with tuneable IRI activity using an external trigger. Collectively, these studies provide substantial insight into the structural features required for the IRI activity of glyco(peptide) and gluconamide IRIs as well as their corresponding impacts on cryopreserved biological samples.
Keywords: Carbohydrate Chemistry; Cryopreservation; Ice Recrystallization Inhibitors